1999
DOI: 10.1126/science.283.5405.1152
|View full text |Cite
|
Sign up to set email alerts
|

A Processive Single-Headed Motor: Kinesin Superfamily Protein KIF1A

Abstract: A single kinesin molecule can move "processively" along a microtubule for more than 1 micrometer before detaching from it. The prevailing explanation for this processive movement is the "walking model," which envisions that each of two motor domains (heads) of the kinesin molecule binds coordinately to the microtubule. This implies that each kinesin molecule must have two heads to "walk" and that a single-headed kinesin could not move processively. Here, a motor-domain construct of KIF1A, a single-headed kines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
407
5
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(441 citation statements)
references
References 33 publications
28
407
5
1
Order By: Relevance
“…In our case, drag created by the MT movement would bias the direction of particle drift. Unlike or Okada and Hirokawa (1999), however, we have never observed that the drifting particles exhibit back-and-forth movement. Alternatively, the antibodies could interact transiently with the substrate or another passing MT.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our case, drag created by the MT movement would bias the direction of particle drift. Unlike or Okada and Hirokawa (1999), however, we have never observed that the drifting particles exhibit back-and-forth movement. Alternatively, the antibodies could interact transiently with the substrate or another passing MT.…”
Section: Discussionmentioning
confidence: 80%
“…A change in viscosity of the medium might then be expected to increase the velocity of drifting, which seems to be the case. In some respects, this phenomenon could be the equivalent of that producing one-dimensional diffusion of MTs described by or of one of the possibilities described for the weak binding state of C351 to MTs by Okada and Hirokawa (1999), where C351 is anchored by an electrostatic potential that restricts its movement away from the MT while allowing free movement along the MT. In our case, drag created by the MT movement would bias the direction of particle drift.…”
Section: Discussionmentioning
confidence: 99%
“…Models of multi-lane TASEP, where the particles can occasionally change lane, have also been investigated analytically [12,13]. Twolane generalizations of generic models of cytoskeletal molecular motor traffic have also been reported [14,15].Recently a quantitative theoretical model has been developed [16, 17] (from now onwards, we shall refer to it as the NOSC model) for the traffic of KIF1A proteins, which are single-headed kinesins [18,19,20], by explicitly capturing the essential features of the mechano-chemical cycle of each individual KIF1A motor, in addition to their steric interactions. In this communication we extend the NOSC model by adding to the master equation all those terms which correspond to lane changing.…”
mentioning
confidence: 99%
“…Recently a quantitative theoretical model has been developed [16, 17] (from now onwards, we shall refer to it as the NOSC model) for the traffic of KIF1A proteins, which are single-headed kinesins [18,19,20], by explicitly capturing the essential features of the mechano-chemical cycle of each individual KIF1A motor, in addition to their steric interactions. In this communication we extend the NOSC model by adding to the master equation all those terms which correspond to lane changing.…”
mentioning
confidence: 99%
“…One explanation of this was given in [2] and it has been suggested as a description of processivity in the KIF-1A family of kinesins, [12], [13]. There is a discussion in [6] as well as the Parrondo Paradox, a coin toss game somethimes thought to mimic molecular motor behavior, in [7].…”
Section: Introductionmentioning
confidence: 99%